12 notes : on life and creativity - Jones, Quincy, 1933-; Smith, Alyssa Lein (Abrams Image, 2022)
"Wisdom and musings on creativity and life from one of the world's most beloved musicians, producers, and mentors, Quincy Jones 12 Notes is a self-development guide that will affirm that creativity is a calling that can and should be answered, no matter your age or experience. Drawing from his own life, and those of his many creative collaborators past and present, Quincy Jones presents readers with lessons that are hardworking and accessible, yet speak to the passion of self-expression. He includes sections as deep as how to transform grief into power, and as practical as how to set goals and articulate intentions through daily affirmations. Weaving his story throughout, Jones lets readers in on his own creative process, as well as the importance of letting honesty, hard work, and good relationships drive your career." --